The Sarda Sheep Host Fecal Proteome. Issue 3 (6th February 2018) - Palomba, Antonio; Tanca, Alessandro; Addis, Maria Filippa; Pagnozzi, Daniela; Uzzau, Sergio
Abstract: The first characterization of the sheep fecal microbiota was recently reported, as obtained by using a multi meta‐omic approach. Here, the mass spectra generated by single‐run LC/high‐resolution MS in the context of that study were reanalyzed using a host‐specific database, in order to gain insights for the first time into the host fecal proteome of healthy Sarda sheep. On the whole, 5349 non‐redundant tryptic peptide sequences were identified, belonging to 1046 different proteins. The "core" fecal proteome (common to all animals) comprised 431 proteins, mainly related to biological processes as immune response and proteolysis. Proteins involved in the immune/inflammatory response and peptidases were specifically investigated. This dataset provides novel insights into the repertoire of proteins secreted in the sheep intestinal lumen, and constitutes the basis for future shotgun and targeted proteomics studies aimed at monitoring changes in the sheep fecal proteome in response to production variables, infectious/inflammatory states, and variations in the gut microbiota. Data are available via ProteomeXchange with identifier PXD006145.